Two new species of Mexican Iridaceae - Espejo Serna, Adolfo; López-Ferrari, Ana Rosa; Ceja Romero, Jacqueline; Cholewa, Anita (Instituto de Ecología, A.C., 2001)
Two new species of Iridaceae are described and illustrated, both collected in the state of Oaxaca, Mexico. Sisyrinchium planicola Ceja & Cholewa has blue flowers with a white eye and grows abundantly in the flood plains of Llano de las Flores. Tigridia mariaetrinitatis Espejo & López-Ferrari, only known from the type locality in Rancho Progreso, municipality of Chalcatongo de Hidalgo, belongs to the subgenus Hydrotaenia and has the flowers erect, brilliant yellow in their base, the outer tepals white lilac with purple spots and the inner tepals yellow with purple spots.